Optimization of total phenolic contents, antioxidant, and in-vitro xanthine oxidase inhibitory activity of sunflower head. Issue 1 (1st January 2018) - Mehmood, Arshad; Zhao, Lei; Ishaq, Muhammad; Safdar, Bushra; Wang, Chengtao; Nadeem, Muhammad
ABSTRACT: Sunflower head ( Helianthus annuus, Asteraceae) is a residual by-product generated during the production of sunflower seed oil and contains a considerable amount of bioactive components. The aim of the present study was to determine and optimize extraction conditions for total phenolic content (TPC), antioxidant activities (DPPH, ABTS and FRAP) and xanthine oxidase (XOD) inhibitory activity of SH. The solute solvent ratio showed a significant effect on yield, TPC, antioxidant activities and XOD inhibition. The Box–Behnken design (BBD) was employed for optimization of extraction parameters (yield, TPC and antioxidant activities). The statistical findings for optimized conditions reveal that the best extraction of SH was obtained with the following parameters: ethanol (54.5%), temperature (72.3°C) and time (138.8 min). This present study may help in the industrial extraction process; moreover, further deep studies are required to optimize sequential steps to increase the efficacy.